Unanticipated Side Effects of Successful Quality Programs: Exploring a Paradox of Organizational Improvement - Sterman, John D.; Repenning, Nelson P.; Kofman, Fred (Management Science, 1997)
Recent evidence suggests the connection between quality improvement and financial results may be weak. Consider the case of Analog Devices, Inc., a leading manufacturer of integrated circuits. Analog's TQM program was a dramatic success. Yield doubled, cycle time was cut in half, and product defects fell by a factor of ten. However, financial performance worsened. To explore the apparent paradox we develop a detailed simulation model of Analog, including operations, financial and cost accounting, product development, human resources, the competitive environment, and the financial markets. We used econometric estimation, interviews, observation, and archival data to specify and estimate the model. We find that improvement programs like TQM can present firms with a tradeoff between short and long run effects. In the long run TQM can increase productivity, raise quality, and lower costs. In the short run, these improvements can interact with prevailing accounting systems and organizational routines to create excess capacity, financial stress, and pressure for layoffs that undercut commitment to continuous improvement. We explore policies to promote sustained improvement in financial as well as nonfinancial measures of performance.